СЕЛЕКТИВНЕ ТА АДАПТИВНЕ ОЦІНЮВАННЯ ГАРМОНІК ДЛЯ ТРИФАЗНОГО СИЛОВОГО АКТИВНОГО ФІЛЬТРА - Пересада, С.М.; Михальський, В.М.; Зайченко, Ю.М.; Ковбаса, С.М. (Інститут електродинаміки НАН України, Київ, 2018)
The paper deals with on-line estimation of three-phase current harmonics on the basis of adaptive control technique. It is shown that standard observer for positive and negative sequences of each harmonic delivers strong selectivity pro-perties, but has limited speed of convergence and it is suitable when not all harmonics are required to be estimated. A novel structure of estimator with measured currents filtration which guarantees fast asymptotic convergence and simple tuning procedure is proposed. A new approach to shunt active power filter current control based on a combination of current control loop and harmonic estimator is also presented. Proposed approach allows to achieve the asymptotic estimation and asymptotic compensation of all set of harmonics. Simulation and experimental results proof the theoretical findings. References 13, figures 7.